The influence of perceived usefulness and perceived ease of use on behavioral intention with TAM approach to users of research management information systems - Liestya Padmawidjaja (Institute of Computer Science (IOCS), 2023)
Along with the increasingly complex and broad scope of research implementation in tertiary institutions, so the development of a research and community service management system based on information and communication technology. The system is called the Research and Community Service Management System. The purpose of this study was to determine the perceived usefulness (PU), perceived ease of use (PEU) and behavioral intention (BI) of research lecturers who use the Research and Community Service Management System at a private university in Java, Indonesia and to determine the perceived influence usefulness (PU), perceived ease of use (PEU) on behavioral intention (BI) in research lecturers who use the Research and Community Service Management System in one of the Private University in Java , Indonesia . This research is a quantitative study using descriptive data analysis and multiple linear regression. The respondents in this study amounted to 66 research lecturers using the Research and Community Service Management System at a private university in Java, Indonesia using a simple random sampling method. The results of this study indicate that perceived usefulness (PU) is at 72.95% in the